Vertical coordination through renegotiation - Özlem Bedre-Defolie (European School of Management and Technology (ESMT), 2011)
This paper analyzes the strategic use of bilateral supply contracts in sequential negotiations between one manufacturer and two differentiated retailers. Allowing for general contracts and retail bargaining power, I show that the first contracting parties have incentives to manipulate their contract to shift rent from the second contracting retailer and these incentives distort the industry profit away from the fully integrated monopoly outcome. To avoid such distortion, the first contracting parties may prefer to sign a contract which has no commitment power and can be renegotiated from scratch should the manufacturer fail in its subsequent negotiation with the second retailer. Renegotiation from scratch induces the first contracting parties to implement the monopoly prices and might enable them to capture the maximized industry profit. A slotting fee, an up-front fee paid by the manufacturer to the first retailer, and a menu of tariff-quantity pairs are sufficient contracts to implement the monopoly outcome. These results do not depend on the type of retail competition, the level of differentiation between the retailers, the order of sequential negotiations, the level of asymmetry between the retailers in terms of their bargaining power vis-à-vis the manufacturer or their profitability in exclusive dealing.
urn:nbn:de:101:1-201201176343
Keywords: 650; vertical contracts; rent shifting; renegotiation; buyer power; Lieferantenmanagement; Einzelhandel; Verhandlungsmacht; Vertragstheorie; Theorie